2017
DOI: 10.1159/000479691
|View full text |Cite
|
Sign up to set email alerts
|

Circulating IGF-I, IGFBP-3 and the IGF-I/IGFBP-3 Molar Ratio Concentration and Height Outcome in Prepubertal Short Children on rhGH Treatment over Two Years of Therapy

Abstract: Objective: To investigate the occurrence of abnormally elevated values of biomarkers of growth hormone (GH) action in short children on recombinant human GH (rhGH) therapy. Methods: Sixty-three prepubertal short children were examined: 31 with GH deficiency (GHD), 25 small for gestational age (SGA), and 9 with Turner syndrome (TS). The main outcomes were the following: standard deviation score (SDS) values of IGF-I, IGFBP-3, and IGF-I/IGFBP-3 molar ratio before, at the 1st and at the 2nd year on rhGH and Δheig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
1
13
0
2
Order By: Relevance
“…We also found that the intervention resulted in increased IGF-I:IGFBP3 molar ratio. The molar ratio between total IGF-I and IGFBP-3 (IGF-I/IGFBP-3) has been suggested to indirectly reflect free as well as with bioactive IGF-I [35,36]. Changes in concentrations of IGFBP-3 and the IGF-I:IGFBP-3 ratio deserve attention as they present potential clinical implications suggested by epidemiological data showing significant associations between IGFBP-3 or the IGF-I:IGFBP-3 ratio and various diseases such as cancer, coronary events, hepatic steatosis, and lung function to mortality [37].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the intervention resulted in increased IGF-I:IGFBP3 molar ratio. The molar ratio between total IGF-I and IGFBP-3 (IGF-I/IGFBP-3) has been suggested to indirectly reflect free as well as with bioactive IGF-I [35,36]. Changes in concentrations of IGFBP-3 and the IGF-I:IGFBP-3 ratio deserve attention as they present potential clinical implications suggested by epidemiological data showing significant associations between IGFBP-3 or the IGF-I:IGFBP-3 ratio and various diseases such as cancer, coronary events, hepatic steatosis, and lung function to mortality [37].…”
Section: Discussionmentioning
confidence: 99%
“…As an easier available surrogate marker, the IGF-I/IGFBP-3 molar ratio has been suggested. It might not provide all the information which could be extracted from direct assessment of free IGF-I, but has been shown to correlate with clinical endpoints such as efficacy of recombinant human GH treatment (70,71).…”
Section: Free Igf-imentioning
confidence: 99%
“…In another study involving 63 children treated with GH, the molar ratio of IGF-I to IGFBP-3, a proxy for free IGF-I levels, was significantly increased in children with an adequate response to GH therapy compared with nonresponders. These studies, albeit limited, support the hypothesis that increasing free IGF-I levels should lead to increased growth [ 11 ].…”
mentioning
confidence: 58%